Tailorable microwave absorption characteristics of bio waste-based composites through a macroscopic design. Issue 11 (5th May 2021) - Bora, Pritom J.; H. S., Meghana Jois; Kumar, T. R. Suresh; Khasnabis, Sutripto; Ramamurthy, Praveen C.
Abstract : Macroscopic designs of dried cow dung loaded polydimethyl siloxane (PDMS) composite for broadband microwave absorption is explored in this study. Abstract : Biologically sourced filler such as a dried cow dung (dielectric)-loaded polydimethyl siloxane (PDMS) composite for broadband microwave absorption is explored in this study. PDMS is a well-known elastomer for electromagnetic (EM) applications due to its numerous advantages of being lightweight, flexible, and corrosion protective, and having facile preparation and large area fabrication. The optimally prepared a 8-mm thick PDMS-cow dung (PC) composite showed a minimum reflection loss (RL) value of −6 dB in the Ku-band (12.4–18 GHz), and it did not meet the percolation limit (RL ≤ −10 dB). In order to enhance the microwave absorption and absorption bandwidth (RL ≤ −10 dB), numerous macroscopic designs, such as pyramidal and multi-layered pyramidal PC composite design were carried out for the same thickness. The optimized multi-layered pyramidal PC composite exhibited more effective absorption, and obtained a minimum RL value of −43 dB, having two specific absorption bandwidth in the frequency range of 8.2–18 GHz (both X-band and Ku-band). Mechanistically, the edge scattering and combined one-fourth resonances as well as high dielectric loss, which led to more storage of electromagnetic energy, were the major contribution factors. Further electromagnetic power loss was more prominent in the multi-layered pyramidal PC composite due to inhomogeneous energy losses. The simulated results were compared to the experimental data and showed the suitability of this composite for real time applications, particularly for defence. This study also indicates that low dielectric composites can be used for real time microwave absorption through different macroscopic designs.